2006
DOI: 10.2174/092986606775101733
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Human B-Casomorphin-7 on Specific Binding of 3H-Spiperone to the 5-HT2-Receptors of Rat Brain Frontal Cortex

Abstract: Using radio-receptor analysis, it has been demonstrated that human beta-casomorphin-7 (Tyr-Pro-Phe-Val-Glu-Pro-Ile) displaces 3H-spiperone from 5-HT2-receptors of rat brain frontal cortex. IC50 of human beta-casomorphin-7 was 8 microM. These data suggest that one of the mechanisms of neurotropic action of beta-casomorphin-7 is might be associated with its influence on the serotoninergic system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…However, it is evident that A1 stimulates production of the enzyme DPP-4 in the rat jejunum through a nonopioid mechanism ( 39 ). It is also known that BCMs are 5-hydroxytryptamine2 (5HT2)-serotonin receptor antagonists through an unrelated mechanism ( 52 – 54 ). Furthermore, recent research has shown that A1 compared with A2 has implications for casein micelle structure and associated chaperone activity within the gastrointestinal system that is unrelated to opioid mechanisms ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is evident that A1 stimulates production of the enzyme DPP-4 in the rat jejunum through a nonopioid mechanism ( 39 ). It is also known that BCMs are 5-hydroxytryptamine2 (5HT2)-serotonin receptor antagonists through an unrelated mechanism ( 52 – 54 ). Furthermore, recent research has shown that A1 compared with A2 has implications for casein micelle structure and associated chaperone activity within the gastrointestinal system that is unrelated to opioid mechanisms ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are no recent studies to confirm this hypothesis. Recently, one research group has suggested a possible interaction of BCM7 with serotonin systems (Sokolov et al, 2005(Sokolov et al, , 2006(Sokolov et al, , 2008.…”
Section: Other Activities Of Food-derived Opioid Peptidesmentioning
confidence: 99%